Comparison of UV and charged aerosol detection approach in pharmaceutical analysis of statins - Nováková, Lucie; Lopéz, Sofía Arnal; Solichová, Dagmar; Satínský, Dalibor; Kulichová, Bohumila; Horna, Ales; Solich, Petr (Talanta, 2009)
CAD (charged aerosol detector) has recently become a new alternative detection system in HPLC. This detection approach was applied in a new HPLC method for the determination of three of the major statins used in clinical treatment-simvastatin, lovastatin and atorvastatin. The method was optimized and the influence of individual parameters on CAD response and sensitivity was carefully studied. Chromatography was performed on a Zorbax Eclipse XDB C18 (4.6 mm x 75 mm, 3.5 microm), using acetonitrile and formic acid 0.1% as mobile phase. The detection was performed using both CAD (20 pA range) and DAD (diode array detector-238 nm) simultaneously connected in series. In terms of linearity, precision and accuracy, the method was validated using tablets containing atorvastatin and simvastatin. The CAD is designated to be a non-linear detector in a wide dynamic range, however, in this application and in the tested concentration range its response was found to be perfectly linear. The limits of quantitation (0.1 microg/ml) were found to be two times lower than those of UV detection.
Keywords: Atorvastatin; aerosoly; simvastatin; vysokoúčinná kapalinová chromatografie; Lovastatin; Heptanoic Acids; tablety; statiny; Aerosols; Chromatography, High Pressure Liquid; lovastatin; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Pyrroles; atorvastatin; zdravotnické prostředky; kyseliny heptylové; Equipment and Supplies; Tablets; pyrroly; Simvastatin